2008
DOI: 10.1017/s1368980008001742
|View full text |Cite
|
Sign up to set email alerts
|

How to achieve long-term breast-feeding: factors associated with early discontinuation

Abstract: Objectives: To evaluate the factors associated with discontinuation of breastfeeding before 12 months in order to make suggestions for achieving long-term breast-feeding. Design: A descriptive cross-sectional study. Setting: Gazi University Medical School, Ankara, Turkey. Subjects: Mothers of 1230 children who discontinued breast-feeding at least 15 d before the last visit were asked to fill out a questionnaire about the discontinuation process. Logistic regression analysis was performed to assess the independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 45 publications
2
16
0
2
Order By: Relevance
“…We found that perception of milk supply was an important factor associated with exclusive breastfeeding in Indonesian mothers. This finding is consistent with previous studies in Turkey [27] and Mexico [9], which reported that the perception of insufficient milk was prevalent in postpartum mothers who did not practice exclusive breastfeeding. In Indonesian culture, mothers tend to believe that small breasts produce smaller amounts of breast milk and older mothers' breast milk is of lower quality [28], which in turn, impact mothers' perceptions of milk insufficiency.…”
Section: Mothers' Perception Of Milk Supplysupporting
confidence: 93%
“…We found that perception of milk supply was an important factor associated with exclusive breastfeeding in Indonesian mothers. This finding is consistent with previous studies in Turkey [27] and Mexico [9], which reported that the perception of insufficient milk was prevalent in postpartum mothers who did not practice exclusive breastfeeding. In Indonesian culture, mothers tend to believe that small breasts produce smaller amounts of breast milk and older mothers' breast milk is of lower quality [28], which in turn, impact mothers' perceptions of milk insufficiency.…”
Section: Mothers' Perception Of Milk Supplysupporting
confidence: 93%
“…Likely to our study, Matich et al reported that educating mothers about breastfeeding together with social support decreased the usage of bottle-feeding (30). In another study from Turkey, it was revealed that introduction of bottle-feeding correlated with the discontinuation of breastfeeding (31). Lowering bottle-feeding decreases the risk of infections and extends the duration of breastfeeding, including exclusive breastfeeding.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies report that primiparous mothers may be more likely to initiate BF ( 36 , 43 ) . However, they are more likely to discontinue BF ( 34 ) , probably due to lower self-efficacy for BF and lack of support ( 24 ) . It is not uncommon for studies to also show that BF initiation ( 37 ) and premature BF discontinuation ( 39 ) are more common among multiparous mothers, or report no differences by parity ( 34 , 44 ) .…”
Section: Discussionmentioning
confidence: 99%